2022
DOI: 10.1038/s41541-022-00586-7
|View full text |Cite|
|
Sign up to set email alerts
|

Titers of antibodies against ancestral SARS-CoV-2 correlate with levels of neutralizing antibodies to multiple variants

Abstract: Diagnostic assays currently used to monitor the efficacy of COVID-19 vaccines measure levels of antibodies to the receptor-binding domain of ancestral SARS-CoV-2 (RBDwt). However, the predictive value for protection against new variants of concern (VOCs) has not been firmly established. Here, we used bead-based arrays and flow cytometry to measure binding of antibodies to spike proteins and receptor-binding domains (RBDs) from VOCs in 12,000 serum samples. Effects of sera on RBD-ACE2 interactions were measured… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Serum IgG anti-receptor binding domain of the SARS-CoV-2 spike protein was measured in BAU/mL, as described by Tran and colleagues. 19 Thawed cryopreserved peripheral blood mononuclear cells were stimulated for 24 h at 37°C in complete medium (RPMI 1640 Medium, 10% fetal bovine serum, 1 mM sodium pyruvate, 1% MEM non-essential amino acids, 12 μg/mL gensumycin (all ThermoFisher Scientific, Waltham, MA, USA), and 50 nM 1-thioglycerol (Sigma-Aldrich, Merck, Darmstadt, Germany) with SARS-CoV-2 spike peptides (Wuhan-Hu-1 strain, and alpha [B.1.1.7], delta, and omicron VOCs), spike and nucleocapsid pools of seasonal human coronaviruses (HCoV-OC43, HCoV-NL63, and HCoV-HKU-1), and cytomegalovirus pp65 peptides ( appendix p 13 ). Brefeldin A (BD Golgi Plug, BD Biosciences, San Jose, CA, USA) was added after 2 h. Activated CD4 T cells were identified by CD40L and TNF-α coexpression and CD8 T cells by IFN-γ or TNF-α expression ( appendix p 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…Serum IgG anti-receptor binding domain of the SARS-CoV-2 spike protein was measured in BAU/mL, as described by Tran and colleagues. 19 Thawed cryopreserved peripheral blood mononuclear cells were stimulated for 24 h at 37°C in complete medium (RPMI 1640 Medium, 10% fetal bovine serum, 1 mM sodium pyruvate, 1% MEM non-essential amino acids, 12 μg/mL gensumycin (all ThermoFisher Scientific, Waltham, MA, USA), and 50 nM 1-thioglycerol (Sigma-Aldrich, Merck, Darmstadt, Germany) with SARS-CoV-2 spike peptides (Wuhan-Hu-1 strain, and alpha [B.1.1.7], delta, and omicron VOCs), spike and nucleocapsid pools of seasonal human coronaviruses (HCoV-OC43, HCoV-NL63, and HCoV-HKU-1), and cytomegalovirus pp65 peptides ( appendix p 13 ). Brefeldin A (BD Golgi Plug, BD Biosciences, San Jose, CA, USA) was added after 2 h. Activated CD4 T cells were identified by CD40L and TNF-α coexpression and CD8 T cells by IFN-γ or TNF-α expression ( appendix p 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…Detection of antibodies to virus proteins: Antibodies to proteins from SARS-CoV-2, the seasonal coronaviruses OC43, HKU1, NL63 and 229E, and Epstein Barr Virus (EBV) were measured as previously described (21,22). Brie y, polymer beads with uorescent bar codes were coupled to neutravidin and then to biotinylated virus proteins (Spike-FL), RBD and nucleocapsid, S1 domains of spike proteins from OC43, HKU1, NL63 and 229E, and the nuclear protein from EBV (EBNA1).…”
Section: Serologic Methodsmentioning
confidence: 99%
“…Beads were pelleted by centrifugation and labelled successively with digoxigenin-conjugated recombinant human ACE2 and anti-Digoxin (Jackson Immunoresearch) conjugated in-house to PE. The beads were analysed by ow cytometry as described above (21).…”
Section: Detection Of Neutralizing Antibodies To Sars-cov-2mentioning
confidence: 99%
“…46 In contrast to previous studies, iant. 54,55 In our study population, we found a strong pairwise correlation between anti-spike IgG concentrations and surrogate virus neutralisation against all tested SARS-CoV-2 subvariants at both timepoints. Spearman's rho was greater at visit 2 compared to visit 1 for all subvariants and greater for wild-type than for each omicron sublineage, respectively.…”
Section: Discussionmentioning
confidence: 59%